First, let's simplify each expression by combining like terms:
A: 9x-3x-4 = 6x-4
B: 12x-4 = 12x-4 (Already Combined terms)
C: 5x+x-4 = 6x-4
When looking at the list of equations, it is clear that only Expression A and C are equivalent. Brianna failed to combine like terms and plug in more points than 0.
I Hope this Helps!
-Sinnamin
Answer:
1, 4/5,2/5
Step-by-step explanation:
y = 5x
Let y = 5
5 = 5x
Divide by 5
5/5 =5x/5
1=x
Let y=4
4 =5x
Divide by 5
4/5 =5x/5
4/5 =x
Let y=2
2 =5x
Divide by 5
2/5 =5x/5
2/5 =x
Answer:
12
Step-by-step explanation:
The smaller triangle seems to have dilated and formed the larger triangle. So, let's find the factor of increase.
9 / 3 = 3, so 3 is the factor of increase.
Now we need to do 4 x 3 = 12
So, ? = 12
<em>Hope that helps!</em>
<em>-Sabrina</em>
Answer:
2 385/3913
i think..
Step-by-step explanation:
Answer:
17.2
Step-by-step explanation:
8 to the power of 2 is 64
19 to the power of 2 is 361
361 - 64 is 297
Square root of 297 is 17.2